Cover Feature: Rational Design of Enzyme‐Modified Electrodes for Optimized Bioelectrocatalytic Activity (ChemElectroChem 19/2019). Issue 19 (5th September 2019) - Zhang, Lin; Carucci, Cristina; Reculusa, Stéphane; Goudeau, Bertrand; Lefrançois, Pauline; Gounel, Sébastien; Mano, Nicolas; Kuhn, Alexander
Abstract : The Cover Feature illustrates the electrochemical conversion of oxygen on a highly ordered macroporous gold wire. The internal pore space being modified with a genetically engineered enzyme, it allows a controlled tuning of the bioelectrocatalytic current and its stability. More information can be found in the Article by L. Zhang et al. onpage 4980 in Issue 19, 2019 (DOI:10.1002/celc.201901022 ).